Infective Endocarditis in Patients With Intestinal Failure: Experience From a National Referral Center. Issue 2 (13th April 2020) - Sawbridge, David; Taylor, Michael; Teubner, Antje; Abraham, Arun; Woolfson, Peter; Abidin, Nik; Chadwick, Paul R.; Lal, Simon
Abstract: Background: Infective endocarditis (IE) is a recognized complication of central line–associated bloodstream infection (CLABSI). Central venous access devices (CVADs) are essential for the delivery of long‐term parenteral nutrition (PN), yet there are no published data as to the prevalence, characteristics and outcomes of IE in this population. Methods: A prospectively maintained database of patients with intestinal failure (IF) types 2 and 3, managed by a national intestinal failure center between January 2010 and December 2018, was analyzed retrospectively and relevant factors extracted from case records. Results: A total of 745 patients with IF and CVADs in situ on admission, or placed during their stay, were admitted over the duration of this study, 640 with type 2 IF and 105 with type 3 IF. Two hundred eighty‐two echocardiograms were performed to investigate potential IE associated with a CLABSI event. Four cases of IE were identified in the entire cohort of 782, 666 catheter days (IE incidence rate: 0.005 per 1000 catheter days and 187 per 100, 000 person‐years for the entire cohort; 0.048 per 1000 inpatient catheter days for acute type 2 IF, 0.0026 per 1000 outpatient catheter days [ie, 99 per 100, 000 person‐years for outpatients with type 3 IF]). Conclusion: IE is rare in the type 3 IF population and a rare consequence of CLABSI in inpatient acute type 2 IF. However, mortality and morbidity are high. Routine echocardiography may not be warranted for investigation of CLABSI unless there is a high risk of IE or a virulent organism is involved.